Why don't students like school? a cognitive scientist answers questions about how the mind works and what it means for the classroom - Willingham, Daniel T. (San Francisco, CA Jossey-Bass, 2009)
Cognitive scientist Dan Willingham has focused his acclaimed research on the biological and cognitive basis of learning and has a deep understanding of the daily challenges faced by classroom teachers. This book will help teachers improve their practice by explaining how they and their students think and learn revealing the importance of story, emotion, memory, context, and routine in building knowledge and creating lasting learning experiences.--from publisher description.
Why don't students like school? -- How can I teach students the skills they need when standardized tests require only facts? -- Why do students remember everything that's on television and forget everything I say? -- Why is it so hard for students to understand abstract ideas? -- Is drilling worth it? -- What's the secret to getting students to think like scientists, mathematicians, and historians? -- How should I adjust my teaching for different types of learners? -- How can I help slow learners? -- What about my mind?
Includes bibliographical references (pages [214]-216) and index.
Keywords: Learning, Psychology of; Effective teaching